How sensitive is corporate debt to swings in commodity prices? - Donders, Pablo; Jara, Mauricio; Wagner, Rodrigo (Journal of Financial Stability, 2018)
Commodity producing corporations have trillions of dollars in outstanding debt. Thus, the recent fall in commodity prices raised concerns about sustainability and systemic risks. Using a global sample (2003- 2015) we measure how corporate bonds react to the underlying commodity price. On average a 10% change in the commodity moves yields-to-maturity by only 15 basis points. This is just a tenth of the sensitivity of stocks returns. Nonetheless, bond sensitivity to commodities is significantly stronger for smaller, leveraged and less profitable firms. Also for short maturity bonds. The type of commodity price change matters too. Sensitivity to price drops is at least five times stronger than to increases. Transitory price changes matter for shorter maturities and leveraged firms. In contrast, longer maturities react more to permanent commodity variations. When firms use hedging derivatives, bonds are less sensitive to all price variations. Hedging mitigates the amplification of commodity shocks, as in Shiller (2008). In conclusion, while debt finance deteriorated with the commodity bust, it hardly dried-up.